Biochemical simulation of mutation synthesis and repair during SARS-CoV-2 RNA polymerization - Oo, Adrian; Chen, Zhenhang; Cao, Dongdong; Cho, Young-Jae; Liang, Bo; Schinazi, Raymond F; Kim, Baek (Virology (New York, N.Y.), 2024)
We biochemically simulated the mutation synthesis process of SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) complex (nsp7/nsp8/nsp12) involving two sequential mechanistic steps that occur during genomic replication: misinsertion (incorporation of incorrect nucleotides) and mismatch extension. Then, we also simulated mismatch repair process catalyzed by the viral nsp10/nsp14 ExoN complex. In these mechanistic simulations, while SARS-CoV-2 RdRp displays efficient mutation synthesis capability, the viral ExoN complex was able to effectively repair the mismatch primers generated during the mutation synthesis. Also, we observed that the delayed RNA synthesis induced by mutation synthesis process was rescued by the viral ExoN activity. Collectively, our biochemical simulations suggest that SARS-CoV-2 ExoN complex may contribute to both maintenance of proper viral genetic diversity levels and successful completion of the viral large RNA genome replication by removing mismatches generated by the viral RdRp.